2017
DOI: 10.4049/jimmunol.1700786
|View full text |Cite
|
Sign up to set email alerts
|

Copper Regulates Maturation and Expression of an MITF:Tryptase Axis in Mast Cells

Abstract: Copper has previously been implicated in the regulation of immune responses, but the impact of this metal on mast cells is poorly understood. Here, we address this issue and show that copper starvation of mast cells causes increased granule maturation as indicated by higher proteoglycan content, stronger metachromatic staining and altered ultrastructure in comparison with non-treated cells, whereas copper overload has opposite effects. In contrast, copper status did not impact storage of histamine in mast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…As shown in Figure 1 B and in agreement with observations made in a previous study in Ref. ( 27 ), incubation of BMMCs with PD98059 caused a profound increase in the metachromatic staining properties of the BMMCs. This effect was evident as early as after 24 h and was clearly visible also after long-term exposure to the MEK1/2 inhibitor (Figure 1 B).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Figure 1 B and in agreement with observations made in a previous study in Ref. ( 27 ), incubation of BMMCs with PD98059 caused a profound increase in the metachromatic staining properties of the BMMCs. This effect was evident as early as after 24 h and was clearly visible also after long-term exposure to the MEK1/2 inhibitor (Figure 1 B).…”
Section: Resultssupporting
confidence: 92%
“…As depicted in Figure 6 A, PD98059 treatment of BMMCs caused a robust increase in the amount of stored trypsin-like activity, a finding that is in agreement with an observation in a previous study in Ref. ( 27 ). This was seen after 3 days of culture and was more pronounced after 5–7 days.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that CD 147 autocorrelation induced by copper targeting is a new tumor therapy strategy [15]. Copper has been involved in the regulation of the immune response and plays an essential role in regulating gene expression and the maturation of fine hypertrophic cells [16]. Copper has excellent antibacterial properties, and it is not easy for bacterial resistance to develop in response to it.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Tpsb2 activation, polyomavirus enhancer binding protein 2 (PEBP2) physically interacts with MITF and synergistically activates the Tpsb2 gene transcription [13]. The MITF mRNA and protein levels were recently shown to be reduced upon copper-mediated phosphorylation of MEK1/2 [16].…”
Section: Introductionmentioning
confidence: 99%